The Role of Modern Football Industry on a Nation's Economy (Journal of Business and Management, 2021)
Football is not just a game of sports, in the modern era football has evolved into something that people referred to as the football industry. The importance of the football industry on a country’s economy is indeed becoming a discussion among scholars, on how huge is the impact of football on the economy. Economy growth has factors that contribute to its increase and one of the aspects that contribute to a nation’s economy is the sports industry, especially football. This research paper will provide information on the empirical study of the relation between economic growth of some samples of European countries and football industries in each of those countries. The data were all taken before the pandemic of COVID-19. The COVID-19 worldwide pandemic has been a major problem for the world’s economy. The football industry has changed its format since then, the way the world enjoys football has been shifted. Therefore, it is worth mentioning that this research study does not show any of the major changes that happened in the pandemic circumstances in European countries as well as the European Super League initiation.Keywords: Sports Event, Modern Football Industry, European Economy